DNA Barcoding for the Identification of Phyllanthus Taxa Used Medicinally in Brazil - Inglis, Peter W.; Mata, Lorena R.; da Silva, Marcos José; Vieira, Roberto F.; Alves, Rosa de B.N.; Silva, Dijalma B.; Azevedo, Vânia C.R. (Planta Medica, 2018)
Plants of the genus Phyllanthus, principally Phyllanthus amarus, Phyllanthus urinaria, Phyllanthus niruri, and Phyllanthus tenellus, are used in Brazilian folk medicine to treat kidney stones as well as other ailments, where the latter two species are listed in the Brazilian Pharmacopeia as quebra-pedra (stone-breaker). However, only P. niruri has been shown to be effective in a clinical setting. Nuclear ribosomal internal transcribed spacer (ITS1 – 5.8S rRNA-ITS2), internal transcribed spacer 2, and chloroplasts rbcL, matK, psbA-trnH, trnL, and trnL-trnF were screened for their potential as DNA barcodes for the identification of 48 Phyllanthus taxa in Brazilian medicinal plant germplasm banks and in “living pharmacies”. The markers were also tested for their ability to validate four commercial herbal teas labelled as quebra-pedra. Using the criterion of high clade posterior probability in Bayesian phylogenetic analysis, the internal transcribed spacer, internal transcribed spacer 2, and chloroplast matK, psbA-trnH, trnL, and trnL-trnF markers all reliably differentiated the four Phyllanthus species, with the internal transcribed spacer and matK possessing the additional advantage that the genus is well represented for these markers in the Genbank database. However, in the case of rbcL, posterior probability for some clades was low and while P. amarus and P. tenellus formed monophyletic groups, P. niruri and P. urinaria accessions could not be reliably distinguished with this marker. Packaged dried quebra-pedra herb from three Brazilian commercial suppliers comprised P. tenellus, but one sample was also found to be mixed with alfalfa (Medicago sativa). An herb marketed as quebra-pedra from a fourth supplier was found to be composed of a mixture of Desmodium barbatum and P. niruri.
Keywords: Phyllanthus; Phyllanthaceae; DNA barcoding; urolithiasis; folk medicine